Effective Targeted Gene Knockdown in Mammalian Cells Using the piggyBac Transposase-based Delivery System - Jesse B Owens; Juanita Mathews; Philip Davy; Ilko Stoytchev; Stefan Moisyadi; Rich Allsopp (Elsevier, 2013)
Nonviral gene delivery systems are rapidly becoming a desirable and applicable method to overexpress genes in various types of cells. We have recently developed a piggyBac transposase-based, helper-independent and self-inactivating delivery system (pmGENIE-3) capable of high-efficiency transfection of mammalian cells including human cells. In the following study, we have assessed the potential of this delivery system to drive the expression of short hairpin RNAs to knock down genes in human cells. Two independent pmGENIE-3 vectors were developed to specifically target knockdown of an endogenous gene, telomerase reverse transcriptase (TERT), in telomerase-positive human immortalized cell lines. As compared with a transposase-deficient vector, pmGENIE-3 showed significantly improved short-term transfection efficiency (~4-fold enhancement, 48 hours posttransfection) and long-term integration efficiency (~5-fold enhancement) following antibiotic selection. We detected a significant reduction of both TERT expression and telomerase activity in both HEK293 and MCF-7 breast carcinoma cells transfected with two pmGENIE-3 construct targeting distinct regions of TERT. Importantly, this knockdown of expression was sufficient to abrogate telomerase function since telomeres were significantly shortened (3-4 Kb, P < 0.001) in both TERT-targeted cell lines following antibiotic selection of stable integrants. Together, these data show the capacity of the piggyBac nonviral delivery system to stably knockdown gene expression in mammalian cells and indicate the potential to develop novel tumor-targeting therapies.